2009
DOI: 10.1016/j.schres.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Eye-blink conditioning deficits indicate temporal processing abnormalities in schizophrenia

Abstract: Theoretical models suggest that symptoms of schizophrenia may be due to a dysfunctional modulatory system associated with the cerebellum. Although it has long been known that the cerebellum plays a critical role in associative learning and motor timing, recent evidence suggests that it also plays a role in nonmotor psychological processes. Indeed, cerebellar anomalies in schizophrenia have been linked to cognitive dysfunction and poor long-term outcome. To test the hypothesis that schizophrenia is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 65 publications
9
63
2
1
Order By: Relevance
“…In agreement with the only other study directly comparing medicated and medication-free patients, 32 our data indicate that patients with schizophrenia show impaired eyeblink conditioning, irrespective of medication status.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the only other study directly comparing medicated and medication-free patients, 32 our data indicate that patients with schizophrenia show impaired eyeblink conditioning, irrespective of medication status.…”
Section: Discussionsupporting
confidence: 92%
“…26 Our results are in agreement with those of Bolbecker and colleagues, 32 who included 13 medication-free patients showing significantly fewer CRs and earlier CR response latencies than controls. The authors also observed no effect of medication in eyeblink conditioning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eyeblink conditioning deficits have been reported in patients with nonmotor psychiatric diseases such as schizophrenia (Bolbecker et al, 2009b), bipolar disorder (Bolbecker et al, 2009a), and attention deficit/hyperactivity disorder (Frings et al, 2010), as well as in a large number of human cases with cerebellar lesions Kronenbuerger et al, 2007). Most of these studies demonstrate that progressive memory deficits occur over time.…”
Section: Ser In Pc Spines Is Important For the Induction Of Cerebellamentioning
confidence: 99%
“…One difference between children with autism and the VPA-exposed rats was that the animals did not display a higher rate of acquisition of conditioned responses. Almost all studies using eye-blink conditioning in human disorders (e.g., schizophrenia, (Bolbecker et al, 2009); mental retardation, (Hogg et al, 1979); Huntington disease, (Woodruff-Pak & Papka, 1996); Fragile X Syndrome, (Tobia & Woodruff-Pak, 2009) show impairment in conditioning ability compared to control subjects. It is therefore surprising that children with autism and rats exposed to VPA in utero display an enhancement of eye-blink conditioning, which might actually lead to the first 'autismspecific' test for between species comparisons.…”
Section: Behavioural Similarities To Autismmentioning
confidence: 99%